Methods for enhancing the reliability and security information collection in real-time control systems - Жуков, И. А.; Дрововозов, В. И. (Problems of Informatization and Control, 2008)
We consider the use of a hybrid multi-pass scheme for the collection of information in real-time control systems , which can increase the safety and reliability of the exchange of information in a wireless sensor network . Ways of improving the reliability and security of information gathering